DEVELOPMENT OF TUTORIAL VIDEO LEARNING MEDIA IN IMPROVING STUDENTS' LEARNING OUTCOMES IN CLASS V SD INPRES MAMAJANG I MAKASSAR CITY - Badruddin Kaddas; Sri Hastati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This study discusses the development of video tutorial learning media in improving the learning outcomes of fifth grade students at SD Inpres Bertingkat Mamajang I, Makassar City. The aims of this study were: (1) To find out the analysis of the needs for the development of video tutorial learning media in improving the learning outcomes of fifth grade students at SD Inpres BertingkatMamajang I Makassar City, (2) To find out the stages of designing video tutorial learning media products in improving class student learning outcomes V SD Inpres Bertingkat l Mamajang I Makassar City, (3) To find out the validity of developing video tutorial learning media in improving student learning outcomes of class V SD Inpres Bertingkat Mamajang I Makassar City, (4) to find out the practicality of developing video tutorial learning media in improving learning outcomes fifth grade students of SD Inpres Bertingkat l Mamajang I, Makassar City, and (5) to determine the effectiveness of the development of tutorial video learning media in improving student learning outcomes of class V SD Inpres Bertingkat Mamajang I Makassar City. This research is a development research using before-after or pretest and posttest taking technique with a total of 16 students. Data collection techniques used are observation, test documentation, and questionnaires. The analysis technique used is descriptive quantitative data analysis technique with the ADDIE development model. The research results show that: (1) the use of video learning media in the learning process creates effective and efficient learning (2) social studies learning outcomes of students by applying video learning media have increased with the average achievement of learning outcomes falling into the good and very good categories , (3) there is an increase in social studies learning outcomes for fifth grade students of SD Inpres Bertingkat Mamajang I, Makassar City.